An investigation of English language teachers’ motivation from an ecological perspective: A case study from mainland China - Xueshan Zhang (PLoS ONE, 2025)
Language teachers’ teaching motivation remains an under-researched area. To address this research gap, this qualitative study explored dynamic changes of English teachers’ teaching motivation in a Chinese public high school by utilizing possible selves theory from an ecological perspective, which is a comprehensive approach that highlights teachers’ agency, values their unique experiences and their interactions with the spatial-temporal context. The concept of possible selves encompassing three distinct aspects: the actual self reflects current self-perception; the ideal self embodies future aspirations, and the ought-to self denotes perceived obligations and duties. Data were collected through semi-structured interviews, teachers’ reflective journals, the researcher’s journal, and various documents (i.e., online information provided by the official website of the local high school and its official WeChat account). Against the backdrop of a plethora of research focusing on the more individualistic ideal self, this study found the prominent role of the ought-to self on teachers’ teaching motivation development because participants strongly internalized the ought-to self. In addition, most of their ideal images were in alignment with the ought-to self. This agreement between ideal selves and the ought-to self enhanced their motivation. The article concluded by suggesting that the concept of possible selves should be utilized in teacher education program design to understand and support teachers’ unique aspirations and obligations.